Technological Progress, the Supply of Hours Worked, and the Consumption-Leisure Complementarity - Andreas Irmen (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
At least since 1870 hours worked per worker declined and real wages increased in many of today's industrialized countries. The dual nature of technological progress in conjunction with a consumption-leisure complementarity explains these stylized facts. Technological progress drives real wages up and expands the amount of available consumption goods. Enjoying consumption goods increases the value of leisure. Therefore, individuals demand more leisure and supply less labor. This mechanism appears in an OLG-model with two-period lived individuals equipped with per-period utility functions of the generalized log-log type proposed by Boppart-Krusell (2016). The optimal plan is piecewise defined and hinges on the wage level. Technological progress moves a poor economy out of a regime with low wages and an inelastic supply of hours worked into a regime where wages increase further and hours worked continuously decline.
Keywords: D91; J22; O33; O41; 330; technological change; capital accumulation; endogenous labor supply; OLG-model